Using Genetically Modified Feedstocks in Broiler Diets; Risks, Perceptions and Facts - Filik, G; Gül, A (Journal of the Hellenic Veterinary Medical Society, 2025)
Chicken meat has significantly contributed to people’s access to animal protein sources in recent times. However, it fails to garner the same importance from experts in various sectors of public opinion. Therefore, the objective is to obtain expert opinions and present facts from their perspective, as opposed to consumer opinions typically collected in studies of broiler chickens that consume genetically modified feed raw materials. In some surveys, certain experts who were selected based on their fields of expertise have been found to make errors. The opinions or views of individuals lacking real knowledge on the subject can have negative impacts on both consumers and their environment, who require access to healthy sources of animal protein, as well as the industry and its employees, who rank among the top 11 worldwide.